O AFETO NA PSICANÁLISE E AS DIFICULDADES DE SUA OPERACIONALIZAÇÃO - Oswaldo França Neto (Affectio Societatis, 2014)
This paper, from the theoretical developments that the term affection (and its surrogate, anguish) had in Freud’s work, tries to establish the character of impossibility of the field to which it refers along with the subjective consequences that may arise. Finally, it proposes a quick articulation —a proposal to be developed in the future— between what has been discussed and the great street manifestations, where a collective subject can be hypothesized